Diversidade e conservação de Aegla leach, 1820 (Crustacea, anomura) em área prioritária para preservação - Mollmann, Victor Hugo dos Santos (2022)
Freshwater crustaceans of the genus Aegla Leach, 1820 are important components of the fauna of rivers, streams, lakes, and caves of several countries in South America, where they are endemic. Currently, the genus is represented by 93 described species, but it is estimated that this number could be much higher, given the cryptic complexes discovered in Aegla paulensis, Aegla longirostri, and Aegla uruguayana. Cryptic species complexes are a taxonomic problem present in several taxa, especially those with morphological conservation, underestimating the real diversity of species, bringing implications in conservation and management of the biodiversity. In Brazil, the southern region concentrates most of the species’ diversity of Aegla, and previous studies have shown that the ecoregions of Upper Uruguay, Tramandaí-Mampituba, and Laguna dos Patos Basin compose a large priority area for eglid conservation, due to the high number of species and phylogenetic diversity, high endemism, and threats to the aquatic habitat. And precisely this threat to the aquatic environment serves as the background for Chapter I, in which we evaluate the preservation of freshwater environments within these priority areas, where four large Protected Areas (PA) are located. Water quality was assessed in 33 sampling sites distributed inside and outside the PAs, through physicochemical and microbiological analysis and detection of pesticides and pharmaceutical compounds, to observe factors that threaten aquatic biodiversity. Water quality did not differ significantly between protected and unprotected sites, but indicated clear pollution, with evidence of sewage inflow, even in well-conserved areas. We found 19 pesticides and five pharmaceuticals in water samples from the analyzed region. All the sampled sites presented at least one pesticide and one pharmaceutical compound, especially 2,4-D, present in 91% of them. The different data sources allowed us to observe that PAs are not enough to mitigate anthropic pressures, and preservation and management measures must take into account the entire watershed since rivers and streams go beyond the limits of PAs. The results provide a context for evaluating the influence of anthropogenic impacts on aquatic biodiversity, especially species of the genus Aegla, since the degradation of aquatic environments is one of the main factors responsible for a large number of species of the genus that are threatened with extinction, and preventive measures for the conservation of the aquatic environment become essential to protect biodiversity. In Chapter II, we accessed the diversity and distribution of Aegla in the priority region specified above, also testing the hypothesis of the existence of cryptic complexes among species in the region. For this purpose, we used species delimitation methods applied to mitochondrial COI gene sequences, together with phylogenetic and morphological analyses. We observed 22 potential new species, divided into three cryptic complex clusters: seven putative species in Aegla jarai, three in Aegla franciscana, and one in Aegla camargoi, plus an impressive 11 other putative species not included in any cluster, evidencing that the real diversity of the group is still largely unknown. Our results indicate that the study region has the highest species richness of Aegla, which makes it an even higher priority for the conservation of the genus and preservation of its habitat. Also, integrative taxonomy is the best way to detect new species in groups with conserved morphology.